Performance of Cooled Cone Grinding Machine in Cocoa Cake Processing - Hendy Firmanto; Edy Suharyanto; . Kuswanto (Indonesian Coffee and Cocoa Research Institute, 2015)
The process of cocoa paste pressing has a function to separate the fatty component of cocoa from its cake. Cocoa paste is further processed into cocoa powder using grinding machine for cocoa cake. The cooled cone type of cocoa grinding machine is used to solve the problem of plug in the maschine caused by melting of fat in cocoa cake due to hot effect as a result of friction in the grinding machine. Grinding machine of cocoa has conical form of cylinder for grinding and stator wall wrapped by source of cold and closed with jacket wool. Research was conducted at Kaliwining Experimental Garden of Indonesian Coffee and Cocoa Research Institute (ICCRI) using cocoa cake containing 26.75% originated from Forastero type of cocoa seed. The capacity and recovery of the machine was influenced by space between rotor cylinder and stator wall. Grinding machine operated at cooling temperature of 25.5oC and space between rotor – stator 0.9 cm and the capacity of 187.5 kg/hour with recovery of 200 mesh cocoa powder as much as 24%. The maximum power of machine required was 2.5 kW with efficiency of energy transfer of 97%. Results of proximate analysis showed that there was no change of protein content, but protein and carbohydrate content increased after processing, i.e. from 5.70% and 59.82% into 5.80% and 61.89% respectively.Key words : cocoa cake, cooling, grinding, cocoa powder